2004
DOI: 10.1081/jas-200052017
|View full text |Cite
|
Sign up to set email alerts
|

Cromolyn Sodium: Fitting an Old Friend into Current Asthma Treatment

Abstract: Cromolyn sodium (Intal) has been available in the United States to treat asthma for more than 30 years. Its clinical efficacy in patients with mild or moderate persistent asthma is well documented, and its extensive clinical record of safety remains unique among antiasthma medications. The history of cromolyn sodium complements the science behind current understanding of asthma pathophysiology. Cromolyn sodium was the first nonsteroid, antiasthma drug that blocked chemical mediator release at the cellular leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Originally, Cromolyn was developed as an anti-inflammatory drug used for prophylactic treatment of bronchial asthma and allergic rhinitis. 29 In addition, it has been reported that Cromolyn binds specifically to other members of the S100 protein family (S100A1, S100A12 and S100A13). 30, 31 Recently, Cromolyn has been shown to block the interaction with RAGE, and to inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, Cromolyn was developed as an anti-inflammatory drug used for prophylactic treatment of bronchial asthma and allergic rhinitis. 29 In addition, it has been reported that Cromolyn binds specifically to other members of the S100 protein family (S100A1, S100A12 and S100A13). 30, 31 Recently, Cromolyn has been shown to block the interaction with RAGE, and to inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…12–15 For this reason, cromolyn is often characterized clinically as a “mast cell stabilizer”, 16 and this drug is now used for the treatment of other diseases thought to involve mast cell activation, including allergic rhinitis, allergic conjunctivitis, and mastocytosis. 17 …”
mentioning
confidence: 99%
“…Considering that all these pharmacological agents are not MC specific being active also on other cell types [81,82], no direct conclusions could be drawn on the role of MCs in EAE by these pharmacological studies.…”
Section: Mast Cells In Cns Autoimmunitymentioning
confidence: 99%